The Utilization Of Social Media Da'wa - Yunita, Yuyun (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
This article discusses the use of social media as a means of preaching. Seeing the many social media that can be used for preaching in the world, it can make it easier for a preacher to convey the contents of his preaching. Preaching is an action that invites people to do good, and the media of preaching is an intermediary tool used to carry out the preaching. With the existence of various social media that can be used to carry out preaching, the existence of social media has motivated many preachers to convey their preaching, using various internet facilities. The emergence of millennial preachers has begun to create Islamic content that is packaged in a relaxed manner in stories of everyday life, and decorated with funny things, and now many preachers convey their preaching with events that are in accordance with the lives of Muslim society, so that millennial preachers now attract a lot of attention from the public. The advancement of technology today certainly brings benefits and impacts to the development of preaching. Many millennials use social media for preaching, which is packaged with current trends such as images and videos. The preaching given is based on originality and contemporary. Originality adheres to Islamic values ​​and is based on the latest discoveries in the present.